Effect of prior haptic virtual reality simulation on preclinical endodontic access cavity preparation - Sánchez-Herrera, Germán; Deeb, Ola; Alfaro-Ochoa, Fernando José; Pérez-Leal, Martín; Palma-Carrió, Cristina; Flacco, Nicla (Frontiers in Oral Health, 2025)
IntroductionHaptic virtual reality simulation (HVRS) has emerged as a promising tool in dental education, supporting technical skill acquisition through interactive and feedback-rich environments. This study evaluated whether using HVRS as a preparatory step enhances student performance in endodontic access cavity preparation and explored students' perceptions of the simulation experience.MethodsForty fourth-year dental students were assigned to two groups. The experimental group received HVRS training using the Simodont® Dental Trainer prior to conventional practice. The control group received only conventional training. All participants performed an endodontic access cavity on a premolar artificial tooth model, which was assessed using a validated evaluation rubric. Students in the experimental group also completed a post-simulation perception questionnaire.ResultsThe experimental group showed significantly higher scores in access cavity shape, roof removal, and internal form (p < 0.05). No difference was observed in damage to the pulpal floor. Most students reported that the simulator improved their understanding of internal anatomy and appreciated the opportunity to practice without risk. However, the majority disagreed that tactile realism matched that of a real handpiece.ConclusionIntegrating HVRS prior to conventional phantom-head training may improve specific technical aspects of endodontic access cavity preparation.